2021
DOI: 10.3389/fendo.2021.763538
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Amino Acid Levels and Bone Mineral Density: A Mendelian Randomization Study

Abstract: BackgroundThis study aimed to explore the association between serum amino acids (AAs) levels and bone mineral density (BMD).MethodsWe performed a two-sample Mendelian randomization (MR) analysis to analyze the associations between the levels of eight AAs and BMD values by using summary-level genome-wide association study (GWAS) data. We applied the MR Steiger filtering method and MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO) global test to check for and remove single nucleotide polymorphisms (SNPs) that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…The role of body EAA content on bone health is inconsistent across various studies. Using Mendelian randomization analysis, Z Cui et al revealed that isoleucine and valine levels were positively associated with total BMD in European adults [ 47 ]. In middle-aged men (31–66 years) with idiopathic osteoporosis, most serum EAAs were not different from that of age-matched controls, except for a significant increase in the threonine level.…”
Section: Relationship Between Body Eaas Levels and Bone Quality In Hu...mentioning
confidence: 99%
“…The role of body EAA content on bone health is inconsistent across various studies. Using Mendelian randomization analysis, Z Cui et al revealed that isoleucine and valine levels were positively associated with total BMD in European adults [ 47 ]. In middle-aged men (31–66 years) with idiopathic osteoporosis, most serum EAAs were not different from that of age-matched controls, except for a significant increase in the threonine level.…”
Section: Relationship Between Body Eaas Levels and Bone Quality In Hu...mentioning
confidence: 99%
“…Specific AAs may preferentially bind to a calcium-sensing receptor, modulate its activation by calcium ions, and thus potentially impact bone turnover. Amino acids are also required for bone marrow stromal cells to promote differentiation into osteoblasts, synthesis of type I collagen, circulating levels of IGF-I and alkaline phosphatase [ 9 , 10 ]. Certain AA types, particularly amino acids from the aromatic group, can stimulate increases in intracellular calcium and ERK phosphorylation/activation and may impact an early stage of osteoclast differentiation by suppressing the attachment of osteoclasts and the resorption process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data demonstrated that AAs should also be viewed as specific and selective signaling molecules in bone cells [ 7 , 8 ]. Bone mass can be elevated by amino acid-induced increases in calcium absorption efficiency, osteoblast proliferation and bone mineralization, synthesis of type I collagen, circulating levels of insulin-like growth factor-I (IGF-I) and alkaline phosphatase, suppressed osteoclast differentiation and reduced bone resorption [ 9 , 10 ]. Certain AA types, particularly amino acids from the aromatic group (phenylalanine, tryptophan, tyrosine) can stimulate an increase in intracellular calcium and extracellular signal-regulated kinase (ERK) phosphorylation/activation [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cadogan et al conducted a study in which they showed that a high consumption of milk (a protein-rich food) improved BMD and overall bone mineral acquisition. However, the evidence of the effects of protein intake on bone health is still weak [ 181 , 182 , 183 ], so further research is needed.…”
Section: Treatment Of Osteoporosis and Novel Approachesmentioning
confidence: 99%